Influences of Taiwan's corporate social responsibility report management policy on the information transparency of its capital market - Tzu-Yun Tseng (Borsa Istanbul Review, 2022)
The management policy for Taiwan's corporate social responsibility (CSR) reporting was changed from elective to partial mandatory. Some companies that have already submitted their reports are also required to undergo assurance provided by accountants. The present study explores the influences of Taiwan's partial mandatory disclosure and partial mandatory assurance management policies for CSR reports on firms' investment to cash flow sensitivity which is used to measure the information transparency of the capital market. The results showed that investment to cash flow sensitivity decreased after mandatory disclosure and mandatory assurance. This implies that the partial mandatory disclosure and the partial mandatory assurance policies for CSR reports have a positive influence on mitigating information asymmetry and agency problems being experienced by firms. It also indicates that Taiwan's partial mandatory disclosure and partial mandatory assurance policies for CSR reports aid in increasing information transparency of its capital market.